Music and Rhymes as Mechanisms for ECCE Learners’ Socio-emotional Intelligence Development - Avosuahi Deborah Arasomwan; Glynnis Daries (E-Journal of Humanities, Arts and Social Sciences)
In South Africa, psychosocial problems resulting from child-headed families, orphaned children, violent homes, neglected children, and single parents have considerably grown. These problems including absenteeism, depression, adolescent pregnancy, and suicide can be prevented by teaching children socio-emotional skills, which are the information, abilities, and attitudes needed to identify and control emotions, set and achieve constructive objectives, empathy for others, and maintaining wholesome social connections. Several studies have examined the impact of songs on young children in both European and African contexts. This study thus examined how Early Childhood Care and Education (ECCE) educators utilize musical pedagogies to enhance students’ socio-emotional skills. Through a qualitative case study involving interviews and observations of MKOs (More Knowledgeable Others), the research explored the educators’ engagement with learners and the use of music in supporting socio-emotional development. Six ECCE educators were selected through purposive sampling, conducting interviews, and analyzing data using thematic analysis techniques. The findings confirm that music and rhymes are effective implementation techniques to support young children’s socio-emotional development, particularly those from rural contexts. The findings have demonstrated that music-based instruction improves ECCE learners’ development of these abilities. Practical implications have been provided for ECCE educators and policymakers, highlighting the importance of incorporating music and rhymes into the ECCE curriculum to support socio-emotional development. Future research can explore the impact of music on children’s socio-emotional development in different contexts and investigate the effectiveness of music-based interventions in supporting children’s all-around development.